Selected lifestyle factors as students transition from secondary school to university in Slovakia - Buková, Alena; Tomková, Petra; Uher, Ivan; Kimáková, Tatiana; Vojtaško, Ľuboš; Salonna, Ferdinand (Frontiers in Public Health, 2024)
Background The study aimed to evaluate self-perceived changes in lifestyle factors, particularly physical activity (PA), following the transition from secondary school to university. A secondary objective was to examine the relationship between lifestyle variables and weekly PA frequency. Key factors assessed included sleep quality, dietary habits, alcohol and tobacco consumption, and PA frequency. Methods The study surveyed 1,665 first-year undergraduate students at Slovak public universities (mean age: 20.73 years, SD ±1.39) using adapted versions of Healthy Lifestyle Questionnaire (CEVS-II) and the Brief Pittsburgh Sleep Quality Index (B-PSQI). Data collection took place between December 2022 and February 2023. Results Significant declines were observed in most lifestyle variables after students transitioned to university. The proportion of students engaging in irregular, or no PA increased from 37% before university to 46% during their studies (p < 0.01). Reports of tiredness upon waking also rose, from 52 to 64% (p < 0.01). Meal frequency decreased, particularly among males, with the percentage of students eating only 1–2 meals per day rising from 9 to 15% (p < 0.05). Conversely, the regularity of breakfast consumption increased, increasing from 65 to 73% (p < 0.01). No significant changes were observed in tobacco smoking habits. Conclusion The findings highlight a notable reduction in PA and other lifestyle factors during the transition to university life. These results emphasize the need for targeted interventions to support healthy behaviors during this critical life phase.